Deacetylation of TFEB promotes fibrillar Aβ degradation by upregulating lysosomal biogenesis in microglia. Issue 6 (21st May 2016) - Bao, Jintao; Zheng, Liangjun; Zhang, Qi; Li, Xinya; Zhang, Xuefei; Li, Zeyang; Bai, Xue; Zhang, Zhong; Huo, Wei; Zhao, Xuyang; Shang, Shujiang; Wang, Qingsong; et al.
Abstract: Microglia play a pivotal role in clearance of Aβ by degrading them in lysosomes, countering amyloid plaque pathogenesis in Alzheimer's disease (AD). Recent evidence suggests that lysosomal dysfunction leads to insufficient elimination of toxic protein aggregates. We tested whether enhancing lysosomal function with transcription factor EB (TFEB), an essential regulator modulating lysosomal pathways, would promote Aβ clearance in microglia. Here we show that microglial expression of TFEB facilitates fibrillar Aβ (fAβ) degradation and reduces deposited amyloid plaques, which are further enhanced by deacetylation of TFEB. Using mass spectrometry analysis, we firstly confirmed acetylation as a previously unreported modification of TFEB and found that SIRT1 directly interacted with and deacetylated TFEB at lysine residue 116. Subsequently, SIRT1 overexpression enhanced lysosomal function and fAβ degradation by upregulating transcriptional levels of TFEB downstream targets, which could be inhibited when TFEB was knocked down. Furthermore, overexpression of deacetylated TFEB at K116R mutant in microglia accelerated intracellular fAβ degradation by stimulating lysosomal biogenesis and greatly reduced the deposited amyloid plaques in the brain slices of APP/PS1 transgenic mice. Our findings reveal that deacetylation of TFEB could regulate lysosomal biogenesis and fAβ degradation, making microglial activation of TFEB a possible strategy for attenuating amyloid plaque deposition in AD.